Characterization of Oct4-GFP transgenic mice as a model to study the effect of environmental estrogens on the maturation of male germ cells by using flow cytometry. Issue 154 (November 2015) - Porro, Valentina; Pagotto, Romina; Harreguy, María Belén; Ramírez, Sofía; Crispo, Martina; Santamaría, Clarisa; Luque, Enrique H.; Rodríguez, Horacio A.; Bollati-Fogolín, Mariela
Highlights: We study changes in male germ cells by exposure to xenoestrogens in Oct4/GFP mouse. Oct4/GFP maturation profile from neonatal period until adult stage was established. Neonatal Oct4 expression increased after perinatal exposure to ethynilestradiol. Sperm count in adult mice was reduced after perinatal exposure to ethynilestradiol. Oct4/GFP mouse is useful to detect changes in male germ cells by xenoestrogens. Abstract: Oct4 is involved in regulation of pluripotency during normal development and is down-regulated during formation of postnatal reservoir of germ cells. We propose thatOct4/GFP transgenic mouse, which mimics the endogenous expression pattern of Oct4, could be used as a mammalian model to study the effects of environmental estrogens on the development of male germ cells. Oct4/GFP maturation profile was assessed during postnatal days -PND- 3, 5, 7, 10, 14 and 80, using flow cytometry. Then, we exposed pregnant mothers to 17α-ethinylestradiol (EE2) from day post coitum (dpc) 5 to PND7. Percentage of Oct4/GFP-expressing cells and levels of expression of Oct4/GPF were increased in PND7 after EE2 exposure. These observations were confirmed by analysis of GFP and endogenous Oct4 protein in the seminiferous tubules and by a reduction in epididymal sperm count in adult mice. We introduced Oct4/GFP mouse together with flow cytometry as a tool to evaluate changes in male germ cells development.